Epitaxially Grown Strained Pentacene Thin Film on Graphene Membrane. Issue 17 (7th January 2015) - Kim, Kwanpyo; Santos, Elton J. G.; Lee, Tae Hoon; Nishi, Yoshio; Bao, Zhenan
<x xml:space="preserve">Abstract</x> Organic‐graphene system has emerged as a new platform for various applications such as flexible organic photovoltaics and organic light emitting diodes. Due to its important implication in charge transport, the study and reliable control of molecular packing structures at the graphene–molecule interface are of great importance for successful incorporation of graphene in related organic devices. Here, an ideal membrane of suspended graphene as a molecular assembly template is utilized to investigate thin‐film epitaxial behaviors. Using transmission electron microscopy, two distinct molecular packing structures of pentacene on graphene are found. One observed packing structure is similar to the well‐known bulk‐phase, which adapts a face‐on molecular orientation on graphene substrate. On the other hand, a rare polymorph of pentacene crystal, which shows significant strain along the c‐axis, is identified. In particular, the strained film exhibits a specific molecular orientation and a strong azimuthal correlation with underlying graphene. Through ab initio electronic structure calculations, including van der Waals interactions, the unusual polymorph is attributed to the strong graphene–pentacene interaction. The observed strained organic film growth on graphene demonstrates the possibility to tune molecular packing via graphene–molecule interactions.